A constituição discursiva da educação de jovens e adultos no Instituto Federal de Goiás a partir das representações de professores de línguas estrangeiras, alunos, coordenadores e documentos institucionais - Heberlein, Maria Carolina Terra (2020)
This research investigated how Youth and Adult Education (YAE) was discursively constituted from the representations in the discourses of coordinators, students and institutional documents, as well as the (self) representations of teachers about what it means to be a teacher of Foreign Language (FL) in this context, at the Federal Institute of Education, Science and Technology of Goiás (IFG). Therefore, this study was based on the concepts of Identity (HALL, 1996; 2000; 2019; TADEU DA SILVA, 1999; 2000; 2019; WOODWARD, 2000; RAJAGOPALAN, 1998; BHABHA, 1998; BAUMAN, 1999; 2003), which is understood, in this work, as a continuous process of construction, characterized as mutable, liquid, modifiable, fragmented, changeable, dynamic and ambivalent; of Representations (HALL, 2013; TADEU DA SILVA, 1999; 2000; 2019; WOODWARD, 2000; CELANI; MAGALHÃES, 2002; TELLES, 2004), which, according to Tadeu da Silva (2019), refer to social meanings produced through discourses; and, also, on Foucault's conception of Discourse (1994; 1995; 1996a; 1996b; 2000; 2003a; 2003b; 2004a; 2004b; 2008), who considers it as practices that create the objects of which they speak (FOUCAULT, 2008). In this regard, the representations, which are produced from discourses, encompass the constitutive elements of identities and are produced from power relations (WOODWARD, 2000). The analysis developed are also based on the conceptions of Post-abyssal Thinking (SOUSA SANTOS, 2010) and Complex Thinking (MORIN, 2015), in order to understand more deeply the complexity that permeates the constitution of Youth and Adult Education. The present research is a case study of a qualitative nature (REES, 2008; YIN, 2009) and of an interpretive approach (LÜDKE; ANDRÉ, 1986; ESTEBAN, 2010). 11 coordinators, 52 students and 18 foreign language teachers (Spanish and English) who are involved in the context of Youth and Adult Education, in the 14 IFG campuses, participated in this investigation. The research instruments selected were: questionnaire, for students; interview, for the coordinators; and questionnaire, interview and narrative production, for FL teachers. The analysis of the institutional documents revealed the presence of representations which praise the diversity of the Youth and Adult Education and value the empirical knowledge of its subjects. The discourses of students and coordinators of Youth and Adult Education showed a series of representations which characterize it as a marginal, subaltern and complex modality. Representations that describe this modality as a lost case, which is not important, which should not exist and which compromises the quality of the institution, were identified. The teachers’ discourses, in their turn, both corroborated these perceptions, as well as unveiled (self) representations that maternalize teaching in the Youth and Adult Education and, consequently, point to a vision of education that is based on tutelage attitudes towards these students. Therefore, the relevance of this study is shown as it made it possible to deeply understand the elements that make up the constitutive complexity of YAE, represented by its intricate socio-historical, economic and cultural context which reveals a strong exclusion and social vulnerability of its subjects. Furthermore, this investigation also helped the participants rethink their challenges and their possibilities of action.